2013
DOI: 10.4103/0301-4738.121067
|View full text |Cite
|
Sign up to set email alerts
|

The effects of renal transplantation on diabetic retinopathy: Clinical course and visual outcomes

Abstract: Purpose:To elucidate the clinical course of diabetic retinopathy (DR) after renal transplantation (RT) in a hospital based cohort.Design:Retrospective study.Materials and Methods:A total of 56 eyes of 28 patients, who had DR and end stage renal disease (ESRD) due to diabetes and had undergone RT, were included in this study. Diagnosis and management of DR was carried out according to early treatment of diabetic retinopathy study (ETDRS) guidelines. DR outcome was defined as worsening if there was >2 step incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…In a study done to assess the course of DR after renal transplant, it was found that renal transplant stabilized retinopathy in the majority (60%) of the diabetic patients and significant improvement in visual acuity was seen during the first 20 months postrenal transplant. [ 42 ]…”
Section: Renal Status and Diabetic Retinopathymentioning
confidence: 99%
“…In a study done to assess the course of DR after renal transplant, it was found that renal transplant stabilized retinopathy in the majority (60%) of the diabetic patients and significant improvement in visual acuity was seen during the first 20 months postrenal transplant. [ 42 ]…”
Section: Renal Status and Diabetic Retinopathymentioning
confidence: 99%
“…Most importantly, however, KTx by itself can stabilise retinopathy. [ 4 , 5 ] Another frequent comorbidity is hypertension (HT), that may damage retinal vessels. That is why fundoscopy is important, particularly with evaluation of retinal vessels.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article titled “The effects of renal transplantation on diabetic retinopathy: Clinical course and visual outcomes.”[ 1 ]…”
mentioning
confidence: 99%